Application of GIS for Flood Modeling on Small Islands: A Case Study of Ternate Island, Indonesia - Stewart Pertuack; Reinhard Nolly Limba; Juan S. I. Septory; Rakuasa, Heinrich (Journal of Scientific Insights, 2026)
Floods are hydrometeorological disasters that occur almost every year in Indonesia, including Ternate City. Floods that occurred in 2024 caused 15 people to be injured, 16 people to die, and as many as 25 units of houses to be affected by this disaster. One of the disaster mitigation efforts is to map flood-prone areas by utilizing GIS and remote sensing data. The variables used consist of elevation, slope, LULC, distance from the river, soil type, and rainfall. This research uses the multicriteria evaluation method, in addition to the multicriteria evaluation method, and also uses weighted linear combination. The results showed that the area in the high flood vulnerability class was 15.08%, or 1,532.92 ha; the medium class was 31.24%, or 3,175.21 ha; and the area in the low flood vulnerability level had an area of 5,454.24 ha, or 53.67%. The built-up land predicted to be affected by future flooding has the largest extent in the high-risk zone, covering 1,147.59 ha or 54.12%, compared to built-up land in the moderate and low-risk zones.. The results of this study are expected to help the Ternate government in overcoming the flood problem there.